Class, Habitus, and the Dynamics of Social Relations of Traders in Diamond Trade in the Martapura Town, South Kalimantan - Hidayat, Yusuf (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This study examines the pattern of social relationships among diamond traders in diamond trade that polarized into patterns of social relationships between small, medium and large traders with their respective values. This study aims to describe the pattern of social relationships between diamond traders and reveal the rules of the underlying game patterns of their social relationships that lead to polarization of social relationships between small, medium and large traders. This study used Buordieu framework especially about Field, Habitus, and Doxa to analyze the phenomena. This research uses qualitative research methods and has been implemented in the town of Martapura, South Kalimantan. In this study, five people were interviewed, consisting of merchants of a large trader, two medium traders and two merchants. The study finds that first, there are three forms of social relations pattern among traders of diamond namely: cooperation relationships between small traders, competition relationships between wholesalers and middle traders in accordance with its position, he develops cooperative relationships while in diamond market and relationships competition when trading outside the diamond market. Second, Each class has its own rules of play in accordance with their capacity in the sale and purchase of diamonds and the rules of this game have become a common consciousness among members of the merchant class so that all members of the group implement these rules spontaneously and without questioning its validity.Penelitian ini mengkaji tentang pola hubungan sosial antar pedagang intan di dalam perdagangan intan yang terpolarisasi menjadi pola hubungan social antar pedagang kecil, menengah dan besar dengan nilainya masing-masing. Penelitian ini bertujuan untuk menggambarkan pola hubungan social antar pedagang intan dan mengungkap aturan-aturan main yang mendasari pola hubungan sosial mereka sehingga memunculkan polarisasi hubungan sosial antar pedagang kecil, menengah dan besar. Tujuan penelitian ini dianalisis dengan menggunakan kerangka pemikiran Buordieu terutama tentang Field, Habitus dan Doxa. Penelitian ini menggunakan metode penelitian kualitatif dan telah dilaksanakan di kota Martapura, Kalimantan Selatan. Dalam Peneltian ini, telah diwawancarai sebanyak lima orang informan yang terdiri dari pedagang seorang pedagang besar, dua orang pedagang menengah dan dua orang pedagang kecil. Penelitian ini menemukan bahwa pertama, ada tiga bentuk pola hubungan sosial antar pedagang intan yaitu: hubungan-hubungan kerjasama antar pedagang kecil, hubungan-hubungan persaingan antar pedagang besar dan pedagang menengah sesuai dengan posisinya, dia mengembangkan hubungan kerjasama ketika berada dalam pasar intan dan hubungan persaingan ketika bertransaksi di luar pasar intan. Kedua, Masing-masing kelas memliki aturan mainnya sendiri sesuai dengan kapasitas mereka dalam transaksi jual beli intan dan aturan main ini telah menjadi kesadaran bersama antar anggota kelas pedagang sehingga semua anggota kelompok melaksanakan aturan-aturan ini dengan spontan dan tanpa mempertanyakan lagi keabsahannya.